قضايا التّحليل التّداوليّ في الدّرس البلاغيّ العربيّ )التّقديم والتّأخير نموذجاً( - مرزوق, فاتح (Université de M'sila, 2017)
The linguistic lesson witnessed many developments, especially those related to modern linguistics, because of the existing relationship between them from the foundations of the foundations, and the sciences that broke into the linguistic lesson of linguistics deliberative, and this science, which laid the rules in the linguistic research in all sciences and sciences attached to the flag It is a great door that reveals to you the mask of hidden and deliberative meaning from its own point of view. It seeks to find the interaction between the two senses, My interlocutor between the speaker and the sage. From this point of view, we answer the following problem: What is the study of the deliberative method of the mechanism of submission and delay? Is there a relationship between the rhetorical lesson and the deliberative analysis of the mechanism of submission and delay?
Keywords: التداولية، التقديم والتأخير، الدرس البلاغي، القصدية، الغرض.